Answer:
(a) B. G(x) is an antiderivative of f(x) because G'(x) = f(x) for all x.
(b) Every function of the form
is an antiderivative of 8x
Step-by-step explanation:
A function <em>F </em>is an antiderivative of the function <em>f</em> if
![F'(x)=f(x)](https://tex.z-dn.net/?f=F%27%28x%29%3Df%28x%29)
for all x in the domain of <em>f.</em>
(a) If
, then
is an antiderivative of <em>f </em>because
![G'(x)=8x=f(x)](https://tex.z-dn.net/?f=G%27%28x%29%3D8x%3Df%28x%29)
Therefore, G(x) is an antiderivative of f(x) because G'(x) = f(x) for all x.
Let F be an antiderivative of f. Then, for each constant C, the function F(x) + C is also an antiderivative of <em>f</em>.
(b) Because
![\frac{d}{dx}(4x^2)=8x](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%284x%5E2%29%3D8x)
then
is an antiderivative of
. Therefore, every antiderivative of 8x is of the form
for some constant C, and every function of the form
is an antiderivative of 8x.
An outlier is a value that is much higher or lower than the rest of the data.
The answer here is .7 because all other values range from 3.1-5.8.
Answer: Sorry, can you repost and comment on this post to reach out to me with a clear pic bc the light is blocking the center of the page
Step-by-step explanation:
3 - 15 = -12
so that is your answer
If the pattern continues, so that each term is separated by a distance of 3, then the sequence is given by the recursive rule
![\begin{cases}a_1=1\\a_n=a_{n-1}+3&\text{for }n>1\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Da_1%3D1%5C%5Ca_n%3Da_%7Bn-1%7D%2B3%26%5Ctext%7Bfor%20%7Dn%3E1%5Cend%7Bcases%7D)
From this definition, we can write
in terms of
:
![a_2=a_1+3](https://tex.z-dn.net/?f=a_2%3Da_1%2B3)
![a_3=a_2+3=(a_1+3)+3=a_1+2\cdot3](https://tex.z-dn.net/?f=a_3%3Da_2%2B3%3D%28a_1%2B3%29%2B3%3Da_1%2B2%5Ccdot3)
![a_4=a_3+3=(a_1+2\cdot3)+3=a_1+3\cdot3](https://tex.z-dn.net/?f=a_4%3Da_3%2B3%3D%28a_1%2B2%5Ccdot3%29%2B3%3Da_1%2B3%5Ccdot3)
![a_5=a_4+3=(a_1+3\cdot3)+3=a_1+4\cdot3](https://tex.z-dn.net/?f=a_5%3Da_4%2B3%3D%28a_1%2B3%5Ccdot3%29%2B3%3Da_1%2B4%5Ccdot3)
and so on, up to
![a_n=a_1+(n-1)\cdot3](https://tex.z-dn.net/?f=a_n%3Da_1%2B%28n-1%29%5Ccdot3)
(notice how the subscript on <em>a</em> and coefficient on 3 add up to <em>n</em>)
or
![a_n=1+3(n-1)=3n-2](https://tex.z-dn.net/?f=a_n%3D1%2B3%28n-1%29%3D3n-2)